2020
DOI: 10.1177/1057083720948463
|View full text |Cite
|
Sign up to set email alerts
|

Creative Musical Activities in Undergraduate Music Education Curricula

Abstract: Music education majors report low exposure to creative musical activities (CMAs) despite increased discourse surrounding the inclusion of CMAs in standards, curricula, publications, and practice. The purpose of this study was to compare preservice music teachers’ (PMT) and music teacher educators’ (MTE) experiences with CMAs. We used an anonymous survey instrument to explore definitions, perceived importance and preparedness, and the incorporation of CMAs within undergraduate music education curricula. MTEs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…We distributed our questionnaire using email lists maintained by national organizations and via Facebook groups, an approach recently taken by other researchers conducting survey research (e.g., Ganschow, 2014; Piazza & Talbot, 2021; Rickels & Brewer, 2017; Silvey et al, 2020; Sims & Cassidy, 2019). The difficulty of calculating a response rate from these kinds of distribution procedures is noted by these and other researchers (e.g., Rickels & Brewer, 2017; Silveira & Hudson, 2015; Silvey, 2011; Silvey et al, 2020; Sims & Cassidy, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…We distributed our questionnaire using email lists maintained by national organizations and via Facebook groups, an approach recently taken by other researchers conducting survey research (e.g., Ganschow, 2014; Piazza & Talbot, 2021; Rickels & Brewer, 2017; Silvey et al, 2020; Sims & Cassidy, 2019). The difficulty of calculating a response rate from these kinds of distribution procedures is noted by these and other researchers (e.g., Rickels & Brewer, 2017; Silveira & Hudson, 2015; Silvey, 2011; Silvey et al, 2020; Sims & Cassidy, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…13 The predominance of WAM also overlooks culturally diverse ways of musicking and "diminishes" creative opportunities and development of skills in analysis, interpretation, performance, and especially creation of music. 14 For these reasons, the perspective that "notational ability"…”
Section: Literaturementioning
confidence: 99%
“…3 This has resulted in the reduction of composition to a subsidiary position against performance and listening. 4 Composition is mandatory for all students in earlier years (ages [12][13][14], ideally forming 33 of the "100 indicative hours" of the music classroom learning experiences. 5 Composition should be taught "weekly in all Australian schools" but is not, due to insufficient teacher training.…”
mentioning
confidence: 99%
“…Inservice teachers in a study by Snell and Stringham (2018) felt similarly unprepared and “generally reported lacking confidence, experience, and previous instruction in how to teach improvisation and composition” (p. 8). Preservice music teachers in research by Piazza and Talbot (2020) noted that most composition and arranging activities happened in their theory and arranging courses, and that these activities were used to better understand a specific style of music instead of as a form of creative expression. This suggests that preservice music teachers are interested in engaging young people in improvisation and composition but lack the experience and education to do so.…”
Section: Why Composition and Improvisation?mentioning
confidence: 99%
“…The process of diagenesis takes both time and pressure, which means preservice teachers need to engage in composition and improvisation on a regular basis throughout their coursework, or the residue of those experiences will blow away before it can solidify into anything more permanent. As Piazza and Talbot (2020) discuss, “consistent integration of creative musical activities may (a) increase confidence among preservice music teachers and music teacher educators to generate new musical products, (b) provide additional opportunities for culturally responsive and inclusive teaching practices, and (c) allow MTEs to share accountability for integrating CMAs across the curriculum” (p. 10).…”
Section: Implications For Music Teacher Educatorsmentioning
confidence: 99%